A CASE STUDY THE MODEL OF EDUCATIONAL ENTREPRENEURSHIP STUDENTS AT AL-AMIEN PRENDUAN SUMENEP MADURA SCHOOL YEAR 2024 - ahid, Musleh W; Musrifah, Siti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In the development of education, education entrepreneurship plays important role in Islamic boarding school. It is because Islamic boarding school focus on students act and will create an ulama generation. Islamic boarding school also provides student with entrepreneurship education for their life after graduated from boarding school. Thus, the role of Islamic boarding school is seen through the economic empowerment of the students. It aimed that the student are not only able to apply their knowledge but also only being independent and creat their own jobs. The problems in this reseasch are: 1. What is the entrepreneurship education model for TMI Female Al-Amien Prenduan ?, 2. What is the impact of entrepreneurship education for TMI female Al-Amien Prenduan?, 3. What are the supproting and inhibiting factors for entrepreneurship education for TMI Al-Amien Prenduan female student? The Methode of this reseach is qualitatif field reseach with a case study approach lacated at  TMI Al-Amien Prenduan boarding school Sumenep Madura. The Data collection adapted from the Miles and Huberman interactive model was carried out through : observation, interview and documentation. While the data analysis used through data reduction, data display and conclution.Then Cheking the validyti of the data source use triangulation and tehniques. The results of this research includes: Education entrepreneurship students at TMI Al-Amien Prenduan is an investment in human resources to provide provisions for life after graduation, The Entrepreneurship Education Model are provided in the form of ISTAMA organization curriculum, training and rihlah iqtishodiyah, Entrepreneurial motivation guidance an Training, Accountability reports as evaluation. The Impact of Student Entrepreneurship Education towards the students are: productive mentality, creative fighter, marketing understanding, entrepreneurial motivation, economic, Achieving  of student Entrepreneurship Education skills. The Supporting factors for TMI Al-Amien Prenduan student Entrepreneurship Education in 2023, the existence of the Islamic Boarding School Program, the interest and enthusiasm of female students, Inhibiting Factors for student  Entrepreneurship Education are the density of boarding school activities and limited time